Modelo experimental para utilização da tecnologia de segunda tela no padrão ISDB-Tb - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The Second Screen is a technology created to offer the viewer the ability to interact with the content through mobile devices using applications created for this purpose. It is a platform that is already being used in cable television and satellite television, on some channels available in this type of business, pay TV. It is also used in available content through Bluray media and movie theaters. Among the new applications and services of the companies in the field of electronic games, there are applications that allow players to transform smartphones and tablets on a second screen to enhance the overall experience of a player compared to controls and challenges of a game. The purpose of this work is to create an interactive application prototype for Brazilian System of Digital Television - SBTVD in the ISDB-TB standard (Integrated Services Digital Broadcasting Terrestrial Brazil), that provides the second screen technology in mobile viewers. For this, it will be carried out changes in the signal generated by content providers to inclusion of the second screen option and creating the necessary conditions for detection, synchronization and use of this technology by the end user at his residence. To check the operation of the proposal, it was set up a test environment with the necessary components to simulate the complete system.
Keywords: Tecnologia de segunda tela; Televisão Digital; Dispositivo Móvel; Padrão ISDB-Tb; Second Screen; Digital TV; Mobile Device; ENGENHARIAS: ENGENHARIA ELÉTRICA